Rights, labour migration and development : the ILO approach (ILO)
This brief presents the perspective of the ILO on the human and labour rights of migrant workers as provided by ILO conventions and international human rights instruments and on the link between those rights, labour migration and development. Thus, it briefly outlines the basic normative framework for the protection of the rights of migrant workers, which includes the 1998 ILO Declaration of Fundamental Principles and Rights at Work and its Follow-up, ILO conventions specifically pertaining to migrant workers, and other conventions which are particularly important to the situation of workers employed in countries other than their own, including on the need to provide decent work at home so that individuals will only have to migrate for work out of choice and not necessity.
Keywords: LABOUR